Recent progress on end-group chemistry of conjugated polymers based on Suzuki-Miyaura catalyst-transfer polymerization - Yang, Hee Seong; Choi, Hae Nam; Lee, In Hwan (Giant, 2023)
Addition of functional groups to the end-group of conjugated polymers is key to preparing conjugated macromolecular building blocks useful for producing architecturally complex soft and hybrid conjugated materials. In this regard, the development of precision synthetic methods for conjugated polymers has paved the way for production of end-functionalized conjugated polymers in high purity. In particular, the recent advances in Suzuki-Miyaura catalyst-transfer polymerization (SCTP) have allowed access to various end-functionalized polymers due to its high polymerization efficiency under mild conditions, enhanced functional group tolerance, and improved initiation system. This review discusses the progress of end-group chemistry of conjugated polymers, focused mainly on the SCTP method.
Keywords: End-group functionalization; Hybrid materials; Suzuki-Miyaura catalyst-transfer polymerization